Study of Wetting Phenomenon During Cooling of Curved Surfaces Using Impinging Water Jets - Akmal, Muhammad (My University, 2004)
Wetting phenomenon during cooling of hot cylindrical specimens using Impinging Jet of water has been studied. Effect of jet velocity, jet diameter, water temperature, specimen surface temperature and surface curvature on propagation of wetting front has been analyzed. Propagation of wetting front correlated well with power function of time. Experiments were conducted at specimen surface temperatures of 250, 500 and 800°C. Water temperatures of 20, 50 and 70 or 75 or 80°C were employed with Jet velocities of 5 and 7.75m/sec. Jet diameters of 3mm and 4mm were utilized during experiments. Propagation of wetting front strongly depends upon water temperature. Wetting front grows faster at low water temperature and high jet velocities. For constant water temperature, growth of wetting front is high with high jet velocities. Velocity of wetting front increases with jet diameter of 4mm when compared with that of 3mm due to increase in mass flow. The influence of jet diameter is greater for low water temperature, low surface temperature and high jet velocities. Effect of jet velocity and degree of subcooling on constant "a" and exponent "n" of the power relation are studied. Constant "a" is found to be linear function of jet velocity and degree of sub-cooling. Exponent "n" appears to be independent of jet velocity but weekly dependent on degree of sub-cooling.
Propagation of wetting front with time was analyzed in comparison with the transient temperature drop of material for different thermocouples embedded at stream wise locations within specimen at a distance of 1mm from surface. Temperature readings were used to predict the propagation of wetting front, which was found to be valid for a distance of 10mm from impingement point.
Effect of surface curvature was analyzed by comparing the results of present study with those reported by previous researchers. Surface curvature was found to have significant impact on propagation of wetting front.
Title: Study of Wetting Phenomenon During Cooling of Curved Surfaces Using Impinging Water Jets, Author: Muhammad Akmal, Location: Thode